Transformation of trading patterns in global agricultural markets - V. V. Stroev; E. N. Smirnov (Вестник университета)
The article analyses the key aspects of changes in international agricultural trade patterns, with the main emphasis on the analysis of modern factors shaping the agricultural market situation. The analysis of international trade is conducted in the context of the need to ensure food security and counteract various exogenous shocks (decreasing crop yields, escalating geopolitical conflicts, food crises). This analysis has allowed us to formulate the main determinants that will have a decisive impact on international agricultural trade in the future. It has been established that as a result of international trade, global demand for agricultural land has decreased, and imports are increasingly used by developing countries to solve food security problems. It is shown that geopolitical restrictions and climatic shocks are a key factor influencing global supply chains and changing patterns of international trade in agricultural raw materials and food. The uncertainties that have arisen make it difficult to adequately forecast global flows of agricultural exports and imports, while the current agricultural policies of countries around the world remain virtually unchanged. In prospective studies of international agricultural trade, considerable attention should be paid to issues of supply stability.